2008
DOI: 10.1038/sj.bjc.6604684
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and the risk of breast cancer: the Ohsaki Cohort Study

Abstract: In a prospective study of 23 995 Japanese women, short sleep duration was associated with higher risk of breast cancer (143 cases), compared with women who slept 7 h per day, the multivariate hazard ratio of those who slept p6 h per day was 1.62 (95% confidence interval: 1.05 -2.50; P for trend ¼ 0.03).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 23 publications
10
150
3
2
Order By: Relevance
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
“…Overall, the total number of participants included was 723,337, with 15,156 reported cancer outcomes. Six studies were performed in USA, three in Japan (Kakizaki et al, 2008b;Weiderpass et al, 2012), and one each from German (von Ruesten et al, 2012), Finland (Verkasalo et al, 2005), and Singapore (Wu et al, 2008). The study samples ranged from 12, 222 to 142, 933, and the median of the follow-up durations is 11.3 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is well established that shift work at night is related to poor sleep quality and shorter sleep duration (49), and the latter has been associated with increased risk for breast cancer (50). Periods of rest and "power naps" during night shifts can increase alertness but there is no evidence that power naps reduce circadian disruption or prevent breast cancer.…”
Section: Rest and Short Sleep Periods During Night Shiftsmentioning
confidence: 99%
“…Melatonin may have an inhibitory effect on gonadal function, including the synthesis and secretion of sex hormones, by promoting the release of gonadotropin-releasing hormone; it also exerts an antiproliferative effect on breast cancer cell lines (32).…”
Section: Lack Of Sleep Linked With Breast Cancermentioning
confidence: 99%